(untitled) (Indonesian Tax Justice Review, 2024)
Tax amnesty programs are frequently employed to increase short-term revenue and expand the tax base, yet their long-term implications for tax justice remain contested. This paper examines Indonesia’s repeated tax amnesty initiatives to assess their impact on taxpayer behavior, compliance norms, and perceptions of fairness. Using legal and policy analysis, the study evaluates whether repeated amnesties undermine horizontal equity by rewarding non-compliant taxpayers. The findings indicate that while amnesties generate temporary revenue gains, their recurrence risks creating moral hazard and eroding trust in the tax system. Compliant taxpayers may perceive unequal treatment, weakening voluntary compliance. The global contribution of this paper lies in providing evidence from a developing country context where tax amnesties are institutionalized rather than exceptional. Indonesia’s experience offers cautionary lessons for policymakers worldwide considering amnesties as a fiscal tool. The study contributes to global tax justice debates by highlighting the tension between revenue pragmatism and fairness, arguing that sustainable compliance requires consistent enforcement and credible sanctions rather than repeated forgiveness mechanisms.